Novel Insights and Therapeutics in Multiple Sclerosis [v1; ref status: indexed, http://f1000r.es/59z] - Catriona A. Wagner; Joan M. Goverman (F1000Research, 2015)
The last twelve years have witnessed the development of new therapies for relapsing-remitting multiple sclerosis that demonstrate increased efficacy relative to previous therapies. Many of these new drugs target the inflammatory phase of disease by manipulating different aspects of the immune system. While these new treatments are promising, the development of therapies for patients with progressive multiple sclerosis remains a significant challenge. We discuss the distinct mechanisms that may contribute to these two types of multiple sclerosis and the implications of these differences in the development of new therapeutic targets for this debilitating disease.